Place Marketing: Macao as the Art City for the Future Direction - Wong Ka I (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

How Social Media Affects the Purchase Intentions of Female Consumers in Macao: Watching Beauty and Cosmetic Product Experience Videos on Youtube - Chan, Velda (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

User intention to adopt mobile payment services in Macau - Lam, Ka Wai (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Why did Uber Fail in Macau? Causes and Consequences of a New Digital Business Model Application - Lai, Weng Ian (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

How Do Chinese Manufactured Products Affect Purchase Intention in a SAR of PRC? The Case of Macao - Silva, Márcio Rossano Pegado da (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Corporate social responsibility in Macau gaming industry - Madureira, Óscar Alberto Correia da Costa (University of Saint Joseph, 2015)
Keywords: Gambling; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Adapting the Unified Theory of Acceptance and Use of Technology 2 (Utaut 2) to Explain Acceptance of Battery Electric Vehicles: Evidence From Macau - Lampo, Alessandro (University of Saint Joseph, 2020)
Vehicles solely powered by electricity are a major technological innovation that combines individual transportation needs and environmental sustainability, yet their market penetration is low. Research has traditionally indicated factors such as the vehicle’s purchasing price, driving range, and charging time as the main barriers to adoption. However, the decision to adopt a technology also depends on what the technology represents to the user; therefore, other factors may be important to explain individuals’ behavior. This study is a quantitative and cross-sectional look at the behavioral intention to adopt battery electric vehicles (BEVs) technology in the context of Macau. The research builds on the unified theory of acceptance and use of technology 2 (UTAUT 2) (Venkatesh et. al., 2012) to explain the characteristics of the local consumers. Besides the addition of image and environmental concern to the theoretical model, the study also put forward and evaluate the construct of technology show-off, an original measure of the visible and experiential characteristics of a technology. A sample of 236 Macau residents was analyzed by structural equation modeling (SEM). The analysis of the data supported the explanatory and predictive power of our model and helped to describe the idiosyncrasies of local residents. The results provide insights related to individual technology acceptance that could be useful in designing more accurate strategies and fostering the uptake of BEVs in Macau or markets that share similarities
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

Modelling the barriers that are preventing e-commerce to thrive – a case study from Portugal, international journal of business excellence - Silva, Susana Costa e; Machado, Joana Costa; Martins, Carla; Duarte, Paulo; Marques, João Alexandre Lobo (International Journal of Business Excellence, 2021)
The identification of barriers for e-commerce to thrive in specific countries is a topic of great interest. This work proposes two models to study the barriers to B2C e-commerce adoption in Portugal, highlighting obstacles less exploited by previous research: the impact of offline shopping pleasure and the influence of the distance to shopping malls on online shopping intent. An online survey was conducted based on different constructs. A multivariate OLS hierarchical regression was used to analyse the proposed models regarding the intention to buy online and the number of online purchases. The results revealed that customer satisfaction is a strong predictor of intent to buy online and that perceived product risk remains a barrier to e-commerce. Consumers living in high urbanised areas have more propensity to buy online. Helpful information is provided regarding the impact of context, culture, product, and individual barriers, showing that multichannel strategies are best suited for success.
Keywords: E-commerce barriers; Online shopping; Portugal; Retail